Chenzhilinus, a new subgenus of Euconnus Thomson (Coleoptera: Staphylinidae: Scydmaeninae) from southern China - Yin, Zi-Wei; Zhou, De-Yao (Zootaxa, 2024)
A new subgenus of Euconnus Thomson, Chenzhilinus subgen. nov., is erected for E. (C.) huapingensis sp. nov. collected from Huaping National Nature Reserve in the southern Chinese province of Guangxi. The new subgenus is morphologically most similar to Euconnus s. str. and appears to represent a derived form of the nominotypical subgenus. Chenzhilinus is primarily characterized by two putatively apomorphic traits: the submentum is clearly demarcated laterally by an additional pair of posteriorly convergent hypostomal carinae; and the aedeagus is devoid of parameres.